1962
DOI: 10.2307/3894761
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Methods for Nutritive Evaluation of Range Forages

Abstract: for their suggestions, to Mr. A. A. Aguirre for his technical assistance, and to the staff of the Hopland Field Station for their cooperation in these investigations. This project partially supported by federal funds from Regional Research Project W-34-Range Livestock Nutrition. aClark, K. W. 1958. The adaptation of an artificial rumen technique to the estimation of the gross digestible energy of forages. Ph.D. Diss. Purdue Univ. 110 pp. Processing Of Inoculum And In Vitro Operation In the first series of tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, Taylor et al (1960) Urness et al (1977) reported that the Tilley and Terry technique yielded dry matter digestion indices that were significantly lower than those of conventional trials. Van Dyne (1962) found good agreement between the Tilley and Terry and nylon bag procedures.…”
mentioning
confidence: 80%
“…However, Taylor et al (1960) Urness et al (1977) reported that the Tilley and Terry technique yielded dry matter digestion indices that were significantly lower than those of conventional trials. Van Dyne (1962) found good agreement between the Tilley and Terry and nylon bag procedures.…”
mentioning
confidence: 80%
“…The use of degradation characteristics as a means of formulating ration combinations for ruminants becomes an aide or guide especially for those nutritionists. Several researchers employing the nylon-bag technique [11] [12] [13] to study ruminant digestion use a specific basal diet so as to minimize any variations between animals and different trial periods within animals. However, while the results gained do indicate relatively dry-matter digestibility (DMD) of forages, Journal of Agricultural Chemistry and Environment they do not represent natural conditions where the animals are free-ranging and there is variation in basal diets and hence in DMD efficiencies.…”
Section: Introductionmentioning
confidence: 99%